Rogue flows : trans-Asian cultural traffic - Iwabuchi, Kōichi, 1960-; Muecke, Stephen, 1951-; Thomas, Mandy, 1959- (Book collections on Project MUSE., 2004)
"Rogue Flows brings together some of the best and most knowledgeable writers on consumption and cultural theory to chart the under-explored field of cultural flows and consumption across different regions in Asia, and the importance of these flows in creating contemporary Asian national identities. It offers innovative possibilities for envisioning how the transfer of popular and consumer culture (such as TV, music, film, advertising and commodities) across Asian countries has produced a new form of cross-cultural fertilisation within Asian societies, which does not merely copy Western counterparts." "Rogue Flows is unique in its investigation of how "Asianness" is being exploited by Asian transnational cultural industries and how it is involved in the new power relations of the region. It is an important contribution to the literature of Asian cultural studies."--Jacket